Analisis Kebutuhan Pembelajaran Era Digital 4.0: Multimedia Anatomi Fisiologi Manusia dengan Model STEM Education di Program Studi Pendidikan Biologi IKIP Budi Utomo Malang - Hidayati, Nuril; Irmawati, Farizha (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Learning media used in anatomy courses in human physiology have not utilized information technology integration. Learning activities carried out are still in the form of discussion presentations by utilizing power point media that tend to less activate the thinking ability of students so that the concept of material delivered is difficult to understand. The purpose of this study was to collect information in the form of fundamental problems in the study of human physiology anatomy so that it can be used as a basis for the preparation of multimedia with the STEM Education model. The method used in this study, namely Research and Development refers to the Thiagarajan development model, namely stage 1 (define) and stage 2 (design). The instruments in this study were (1) interview transcripts, (2) observation transcripts, (3) questionnaires, and (4) documentation. The results of the needs analysis show that as follows (1) 31.75% anatomical learning of human physiology is less interesting in terms of models and learning media. (2) 7.14% of students have known the STEM Education model. (3) 88.10% of students need learning media integrated with information technology and learning models that familiarize them with critical thinking skills. (4) human physiology anatomy subjects suggest using multimedia with the STEM Education model that matches the characteristics of students and the curriculum used. Based on the results of the above research it can be concluded that it is very necessary to develop multimedia anatomy of human physiology with the STEM Education model. Suggestions for further research are to carry out a multimedia design that is integrated with technology based on student characteristics and stimulates students' critical thinking skills.